Technical efficiency analysis of China’s agricultural industry: A stochastic frontier model with panel data - Ji Ma (2018)
© Springer International Publishing AG 2018. This paper imposed the translog stochastic frontier production model to analyze the China’s province-level agriculture productivity by using panel data during 2002–2012 on 31 provinces in China. The results show that China’s province-level agriculture productivity has been improved for over 11 years. Hunan, Bejing and Shanghai approached the agriculture technical efficiency frontier. The agriculture technical efficiencies in underdeveloped area such like Guizhou, Yunnan and Anhui increased sharply and approached to the national province-level mean, 60%, in terms of the technical efficiencies over 11 years which, however, still have 40% space to be improved. We recommend that the provinces with lower technical efficiency, such as Anhui, Yunnan and Guizhou, should learn experiences from those provinces that have high technical efficiency so that improving the agricultural productivities of themselves.